The "Pro-Race" chainring: toward an optimization of cycling performances.
Purpose and Methods :This study was designed to compare the mecanichal, physiological and performance responses of cyclists riding with two different chainring designs, round or eccentric, during a brief and intense cycling exercice : an all-out 1-km cycle test on a velodrome. The eccentrically designed chainring was made of two crank arms sliding into each other, with the inside arm fixed on the center of the arm of a circular chainring and the outside arm sliding along the inside and revolving around an elliptical cam. This design increases crank arm lengh at the downstroke and decreases it during the upstroke, thus increasing and decreasing the torque. In terms of the chainring's revolution, the crank arm lengh at 0° and 180° is similar to the arm lengh of circular chainrings (175mm). However, during the downstroke (0°-180°), it increases to its maximum lengh of 200 mm at 90° and then returns to its original lengh of 175 mm at 180°. During the upstroke, it decreases to a minimum lengh of 150 mm at 270° and then increases to 175 mm at 360°. Twelve cyclists performed an all-out 1-km velodrome cycle test using each chainring. The study was conducted over two consecutive weeks with the order of chainring use randomized. Results : None of the physiological (lactate, [La -], heart rate HR) and mechanical (cadence) variables showed significant differences between chainring trials in terms of average values. The time saved with the eccentric chainring was significantly correlated to the muscle volume of the inferior members (r =-0.605 ; P=0.037) and the muscle volume of the calf (r =-0.754 ; P=0.005) (Figs. 1 and 2). Thus, using forward multiple regression, the two factors which best predicted the all-out 1km on a velodrome test with the eccentric chainring were the muscle volume of the inferior members (r = - 0.703 ; P=0.01) and the muscle volume of calf (r = - 0.772 ;P =0.003) (Figs. 2 and 3). Conclusion : It seems that the use of the pro-race would allow on the mechanical level the production of a higher peak torque during downstroke. The eccentric chainring seems to facilitate the patterns of pushing involved in cycling rather than the patterns of pushing-traction. In other words, the cyclists who are the most prone to push hard would have a significant advantage in performing with the pro-race.